The geography of the shredder market in Curitiba, PR, Brazil: a spatial analysis based on the National Law of Schreders (Terr@ Plural, 2022)
Is there a relationship between commercial locations and crimes against high-value property, specifically vehicles? To answer this question, we analyze the used vehicle and parts market, a segment regulated by the National Dismantling Law - Law # 12,977/2014, for the control with greater rigor of the activities of dismantling, sale, and resale of parts and used vehicles. In Paraná state Decree # 8,804/2018 requires accreditation of this type of trade, “shredder”, with the National Department of Transit - DETRAN. Thus, we analyzed the spatial correlation between the occurrencesof vehicles recovered from crime in Curitiba and the points of trade related to dismantling, pointing out areas of high casuistry of occurrence and possible relations with areas of concentration of automotive establishments of parts and used vehicles not yet regularized with DETRAN. A clear similarity was observed between some of the variables distributed by neighborhood, such as “partially legalized chop shops” and “recovered vehicles” (r=0.365). It can be concluded that the Law of the AutoDismantlers brought evident contributions to economic and social development, once contributed to the expressive fall of patrimonial crimes against vehicles in several states, also in Paraná. The results may alert the state to a greater and better commercial inspection of those establishments in its territory.